SIKAP MAHASISWA TERHADAP PROGRAM MAGANG DI MASA PANDEMI COVID-19 DENGAN PENDEKATAN LINGUISTIK SISTEMIK FUNGSIONAL - Sari, Arum Manggar; Mahmudah, Mahmudah; Hajrah, Hajrah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to describe data that includes a musty attitude, judgment, and appreciation of the assessment system on the speeches of Indonesian Language and Literature students Class of 2018 who have participated in internship practices. This type of research is descriptive qualitative. The results of research on student speech found affective attitudes, judgments, and appreciation in the form of positive and negative speech. The results of the study were dominated by negative affect caused by the policies set on the implementation of the internship. on the attitude of judgment leads to the form of politeness in the respondent's language in policies that are motivated by the academic environment and announcing the existence of a pandemic. As well as a positive appreciation of gratitude for the benefits obtained by respondents during internships.